Risk factors of non-communicable diseases in Malaysia / Lim Ooi Wei - Lim , Ooi Wei (2019)
The invasion of urbanization and western lifestyle have led to an increasing trend of Non-Communicable Diseases (NCDs) in Malaysia. Therefore, it is essential to tackle modifiable risk factors of NCDs based on NCD non-modifiable risk factors from different cultural backgrounds and to provide insight for policy makers to develop the most cost-effective strategies for the prevention and control programs of NCDs in Malaysia. This study is targeted to explore the (i) modifiable risk factors of NCDs, (ii) non-modifiable risk factors of NCDs by examining the odds of the risk factors and finally, (iii) to examine the odds of modifiable and non-modifiable risk factors on different outcome levels of NCDs in Malaysia. A nationwide representative secondary data consisting of 28,498 respondents has been used. Odds ratio with 95% confidence interval has been estimated using multinomial logistic regression. The main findings suggest that, obese, overweight and physically inactive respondents increase the likelihood of having all outcome levels of Diabetes Mellitus: Impaired Fasting Glucose (IFG), Newly Diagnosed and Known Diabetes Mellitus (DM). Inadequate fruit and vegetables consumption respondents are more likely to be diagnosed as Newly Diagnosed Diabetes Mellitus patients. However, higher chance of being exposed to Known DM has been observed among ex-smokers. Lower educated group, higher income earners, Indians and retirees are found more likely to be diagnosed as Newly Diagnosed and Known DM patients. Likewise, home makers reveal higher likelihood of having Known DM. Obese and overweight respondents exhibit increased likelihood of having all outcome levels of Hypertension: Newly Diagnosed and Known Hypertension. Physically inactive, ex-smokers and unclassified drinkers are found more likely to be diagnosed as Known Hypertensive patients. However, current drinkers are found to have higher likelihood of Newly Diagnosed Hypertension. With regard to non-modifiable risk factors, elderly, retirees, home makers and lower educated respondents have been identified as more likely to be diagnosed as new hypertension patients. Likewise, the likelihood of having Known Hypertension also has been found to increase significantly among the elderly and other Bumiputra. Physically inactive, current drinkers, unclassified drinkers, ex-drinkers and inadequate fruit and vegetables consumption respondents are found more likely to be diagnosed to have Known Hypercholesterolemia. On the other hand, current smokers, obese and overweight respondents reveal higher likelihood of having Newly Diagnosed Hypercholesterolemia. Among the non-modifiable risk factors, the results of this study exhibit that Indians, lower educated group and retirees show higher likelihood of having Known Hypercholesterolemia. Widows/widowers/divorced respondents and home makers are more likely to be diagnosed as Newly Diagnosed Hypercholesterolemia patients. However, females and higher income earners reveal higher likelihood of having Newly Diagnosed and Known Hypercholesterolemia. The occurrence of different outcome levels of NCDs among the elderly and retirees as well as lower educated group would undeniably create deadweight loss and reduce welfare, utility and their quality of life. This would eventually increase the burden on healthcare cost for Malaysians in the future. Hence, these findings serve as a good benchmark for the Government to allocate resources more efficiently especially to elderly and retirees in Malaysia.